Improvement of wheat (Triticum aestivum L.) yield by different row spacings and varieties - Singh, Bhagat; Kumar, Mukesh; Dhaka, Anil Kumar (Journal of Cereal Research, 2017)
A field experiment was conducted at CCS Haryana Agricultural University, Hisar during rabi 2011-12 and 2012-13 to study improvement of wheat (Triticum aestivum L.) yield by different row spacing and varieties. Three wheat varieties viz. DBW 17, PBW 550 and WH 711 with four row spacings (15.0, 17.5, 20.0 and 22.5 cm) were studied in experimentation split plot design. Results of the experiment revealed that all parameters including growth, yield and yield attributes were significantly influenced by different row spacings. Based on pooled mean data, maximum plant height (90.8 cm) and effective tillers/m2 (481) were recorded in 15.0 cm row spacing crop, which were significantly higher than wider row spacing whereas, highest 1000 grain weight (42.7 g) and grains/earhead (41.9) were observed in 22.5 cm row spacing. The highest grain yield (54.0 q/ha) and straw yield (84.7 q/ha) were recorded when crop was sown at 15.0 cm row spacing, which was significantly higher than 20.0 and 22.5 cm row spacing crop. Among the cultivars, WH 711 recorded highest 1000 grains weight (43.5 g), whereas maximum grains/earhead were recorded in PBW 550 (41.9). Maximum grain yield (52.7 q/ha) was recorded in PBW 550 though the differences were non significant among different varieties, whereas, maximum straw yield (83.9 q/ha) was found in WH 711. Harvest index of PBW 550 (40.1) was significantly higher than DBW 17 and WH 711. DOI:10.25174/2249-4065/2017/66727